(untitled) (Global Journal of Science Frontier Research, 2012)
Based on the big bang concepts - in the expanding universe, rate of decrease in CMBR temperature is a measure of the cosmic rate of expansion. If universe is accelerating, CMBR temperature must decrease continuously. It is noticed that, Bohr radius of hydrogen atom, quanta of the angular momentum and the fine structure ratio - are connected with the large scale structure of the massive expanding universe. In the accelerating universe, as the space expands, in hydrogen atom, distance between proton and electron increases and is directly proportional to the size of the universe. ’Rate of decrease in the laboratory fine structure ratio’ is a measure of cosmic rate of expansion. Considering the integral nature of number of protons (of any nucleus), integral nature of ℏ can be understood. Obtained value of the present Hubble constant is 70.75 Km/sec/Mpc. Instead of the Planck scale, initial conditions can be represented with the Coulomb scale. Finally it can be suggested that, if the primordial universe is a natural setting for the creation of black holes and other non-perturbative gravitational entities, throughout its journey, the whole universe is a primordial (growing and rotating) black hole.